Strategi Manajemen Kurikulum yang Berorientasi pada Hasil Belajar di Sekolah Kreatif SD Muhammadiyah 20 Surabaya - Rachmania, Salsabilillah; Nabilla, Farzha; Therapi, Berlian; Herdha, Romeo; Amalia, Kaniati (Lembaga Yasin AlSys, 2024)
Integrated Curriculum Management refers to planning, developing, implementing and assessing curriculum in educational institutions by identifying learning objectives, teaching materials, teaching methods and reference materials that will be used in the curriculum. The purpose of this article is to examine the curriculum management system at school Creative SD Muhammadyah 20 Surabaya. This includes developing, implementing and evaluating curricula to increase their effectiveness. By using Qualitative Descriptive Methodology as well as Observational Data Collection Methods and Literature Review, the research results show that: (1) Curriculum that supports faith, noble morals, extracurricular and scouting programs (2) Aspects that are relevant to the Education Implementation Report (3) The influence of the curriculum on student growth in primary and secondary schools. Curriculum management includes planning, developing, implementing and assessing curriculum at school or at home. In this abstract, topics will generally be discussed such as curriculum planning, curriculum selection, curriculum implementation, resource management, how the curriculum is implemented in schools, improving the curriculum, the advantages and disadvantages of the curriculum, and how to overcome the shortcomings that occur. , how does the curriculum affect schools, what are the positive and negative impacts of the curriculum, and how to evaluate it to increase its effectiveness.